2016
DOI: 10.1074/jbc.m116.729525
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule Force Spectroscopy Reveals the Calcium Dependence of the Alternative Conformations in the Native State of a βγ-Crystallin Protein

Abstract: Although multidomain proteins predominate the proteome of all organisms and are expected to display complex folding behaviors and significantly greater structural dynamics as compared with single-domain proteins, their conformational heterogeneity and its impact on their interaction with ligands are poorly understood due to a lack of experimental techniques. The multidomain calcium-binding ␤␥-crystallin proteins are particularly important because their deterioration and misfolding/aggregation are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…We are not the only ones to observe specific divalent cation-binding interactions within the β-subtype. In a study using a β-crystallin homolog, protein S sequenced from Myxococcus xanthus , Scholl et al found that the presence of calcium stabilizes a single conformation of the N-terminal domain ( 77 ). Without calcium, the N-terminal domain can adopt two alternative conformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not the only ones to observe specific divalent cation-binding interactions within the β-subtype. In a study using a β-crystallin homolog, protein S sequenced from Myxococcus xanthus , Scholl et al found that the presence of calcium stabilizes a single conformation of the N-terminal domain ( 77 ). Without calcium, the N-terminal domain can adopt two alternative conformations.…”
Section: Discussionmentioning
confidence: 99%
“…This function appears to be evolutionarily conserved in the double Greek-key-folded structure ( 14 , 74 , 84 , 87 ). The major effect of cation binding in these other proteins is the increased thermodynamic, kinetic, and mechanical stability ( 72 , 74 , 75 , 77 , 85 , 86 ). The ability of lens β-crystallins to bind calcium has been speculated as a protective and homeostatic function.…”
Section: Discussionmentioning
confidence: 99%
“…In the middle of the 20th century, Flory and other pioneers put forward several statistical mechanical models to semiquantitatively describe the single-chain elasticities of polymers in theory. , With the advent of single-molecule atomic force microscopy (AFM), the elastic behaviors of individual macromolecules have been extensively researched experimentally since the 1990s. Although great progress has been made toward understanding the single-chain properties of macromolecules, many challenges still remain in this field. With a backbone and side chains, a polymer chain is more complex than a small molecule. Moreover, a single polymer chain is usually placed in a complicated environment such as solvent, cosolute, and solid surface, which significantly affects the behaviors of the chain.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule methods are often advantageous because they minimize opportunities for proteins to aggregate during unfolding measurements of individual molecules. Thus, single-molecule experiments (such as single-molecule force spectroscopy, reviewed in (24)(25)(26)(27)(28)(29)(30)) combined with computer simulations (such as molecular dynamics (MD)) have become excellent tools to precisely characterize the unfolding pathways of complex multidomain proteins (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…One of the simplest SMFS methods is atomic force microscopy (AFM)-based SMFS, also known as atomic force spectroscopy (AFS). This technique has already proven very useful in examining proteins' unfolding and refolding pathways and capturing important details such as transient unfolding intermediates (61) while minimizing protein aggregation (31), making it an ideal tool for studying the mechanical stability and unfolding-refolding behavior of multidomain proteins. Recent improvements by the Perkins group in AFS force resolution and stability and the development of new powerful assays for specific attachment of molecules have significantly increased the AFS success rate, making AFS also ideally suited for studying mechanically weak and fast folding proteins (62,63).…”
Section: Introductionmentioning
confidence: 99%